Website Based Student Violation Information System in Man Karangasem with WhatsApp Notifications - Auril Nisa, Zelica; Baijuri, Achmad; Azise, Nur (Universitas Muhammadiyah Riau, 2024)
The use of information technology is important to education throughout the world, encouraging schools to embrace technological advances. At MAN Karangasem, violations committed by students are still processed manually, resulting in delays in reporting and communication with parents. As part of this investigation, a system was developed to track student misconduct online. The system uses WhatsApp notifications for effective management and reporting. The development follows the Software Development Life Cycle (SDLC) through investigation, observation, interviews and documentation, using a waterfall methodology. This system has proven effective in helping students enter data, search for information, and report violations with a high level of accuracy. WhatsApp notifications speed up notifications to parents and improve communication between schools and parents. This system is expected to be able to overcome existing obstacles in dealing with student violations at MAN Karangasem schools. However, implementation of these systems requires ongoing evaluation to ensure long-term effectiveness and reliability.Suggestions for further research include conducting a comprehensive study of the impact of this system on improving student discipline, school management efficiency, and school-parent relationships.The use of information technology in schools not only changes the way students deal with bad behavior, but also strengthens the relationship between the school and the entire educational community. By using the right technology, MAN Karangasem and other schools can optimize the use of resources and strengthen their commitment to inclusive and results-oriented education.